P-15 Impact of COVID19 on patient outcomes within an acute palliative care service. (20th March 2022) - Spriggs, Helena; Atkinson, Kate; Frew, Katherine
Abstract : Background: The COVID19 pandemic had wide ranging effects on healthcare services and systems within the NHS. There was a particular impact on the Specialist Palliative Care Hospital Liaison Service (SPCHLS) caseload in Northumbria Healthcare NHS Foundation Trust. Our objective was to determine the impact of the COVID19 pandemic on patient outcomes, time from admission to death and place of death. Methods: A retrospective analysis of patients admitted in January 2020 and 2021, with a palliative code on discharge or death. Results: More patients were referred to and seen by SPCHLS in January 2021 compared to January 2020 (n=70 vs 54) and of those patients, more died as an inpatient in January 2021 compared to 2020 (57% vs 37% respectively). 40% of patients died within 10 days of admission in January 2021 compared to 30% in 2020. Of those patients who died within 100 days of admission, less patients died at home in 2021 13% vs 38%. However, more died on a specialist palliative care unit 36% vs 23%. Conclusions: During the COVID19 pandemic more patients were referred to and seen by the specialist palliative care hospital liaison service. There were significantly more deaths and time to death from admission was significantly shorter. More patients died in an acute hospital setting and on specialist palliative care units, with a reduction in transfers to independent hospices. There is a need for continued investment and development of acute palliative care to reflect a potentially sustained change in services, and the requirement to increase the provision of high quality end-of-life-care in hospitals.